The Fulfillment of the Rights of Disabled Prisoners in Correctional Institutions - subrotro, mitro; Novanotona, Steven (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research aims to identify the challenges faced by elderly prisoners in correctional institutions related to declining physical abilities and mental health, analyze the role and effectiveness of independence development programs in helping elderly prisoners overcome these challenges and evaluate the benefits of developing independence for elderly prisoners, including improving the quality of life and their readiness for social reintegration after release. The findings show that mental health problems such as depression and anxiety are also more common among elderly prisoners, which are often exacerbated by social isolation and uncertainty about the future. This research uses a qualitative approach with a literature review method. A literature review was carried out to collect and analyze information from various literature sources that are relevant to the topic of fostering the independence of elderly prisoners. The results of the research can develop and implement a comprehensive and sustainable independence development program for elderly prisoners and involve medical personnel